Guinness world records 2015 - Glenday, Craig; Guinness World Records Limited ([London] Guinness World Records, 2014)
Lists records, superlatives, and unusual facts in the areas of fame, business, crime, the natural world, technology, war, the arts, music, fashion, and sports.
Introduction -- Diamond -- Space -- Earth -- Living planet -- Humans -- Recordmania -- Modern world -- Great journeys -- Arts & media -- Technology and engineering -- Sports.
"All new augmented reality, see it 3D" --Cover.
Keywords: World records; Curiosities and wonders